A systematic literature review on civic engagement program through citizenship education - Maulana, Muhammad Yunus; Milanti, Ajeng Ayu (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Essentially, project-based learning, currently referred to as a method for citizenship education in higher education, is rooted in the concept of civic engagement, which is the most critical determinant of success in transitioning to adult citizenship. Given the limited involvement of the younger generation in public life, which often remains tokenistic and lacks significant impact on change. With their current capacity, young citizens are considered insufficiently equipped to address the challenges of Indonesia’s democratic transition, including the dissemination of disinformation and diminishing political efficacy. Giving precedence to civic engagement programs in citizenship education becomes imperative to fortify democracy. Thus, the refinement of concepts and instructional methodologies for citizenship education requires a comprehensive review of scholarly articles. This research attempts to bridge the gap in systematic literature reviews on this subject, which have not thoroughly examined articles addressing civic engagement programming in terms of concepts and methods. The study employs a systematic literature review methodology, using articles published in Scopus-indexed journals over the past decade as primary sources. This systematic literature review effectively underscores the extensive progress in the concepts and methodologies of civic engagement programs within citizenship education, signaling a promising trajectory in this field. Furthermore, the review identifies pivotal areas for future research, including the fine-tuning of assessment models for experiential-based instruction and a critical reevaluation of the role of civics education in heightening citizens’ political consciousness.